5(x+1)=6x+8

Simple and best practice solution for 5(x+1)=6x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+1)=6x+8 equation:


Simplifying
5(x + 1) = 6x + 8

Reorder the terms:
5(1 + x) = 6x + 8
(1 * 5 + x * 5) = 6x + 8
(5 + 5x) = 6x + 8

Reorder the terms:
5 + 5x = 8 + 6x

Solving
5 + 5x = 8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 5x + -6x = 8 + 6x + -6x

Combine like terms: 5x + -6x = -1x
5 + -1x = 8 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -1x = 8 + 0
5 + -1x = 8

Add '-5' to each side of the equation.
5 + -5 + -1x = 8 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 8 + -5
-1x = 8 + -5

Combine like terms: 8 + -5 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| 5(x-1)=6x+8 | | 7/2x-11/2=17/2 | | 1.3=x^2+0.3 | | 9+3(x-2)=9-4(x-9) | | 1.4q-6.1q+1.4=-26.8 | | 2(x+2)+x=2(x+1)+1 | | 1.4q-6.1+1.4=-26.8 | | 9+2cosx=10 | | r=Ct+a | | m^2-7.5=92.5 | | 7/5y=26/15 | | ((x-3)/6)=2-x | | 3+7x^2+10=0 | | 7/5z-38/45=53/45 | | x-3/6=2-x | | 52/51/91/34 | | -16x^2+14x+13.5=5 | | -(1/2)=x^-2 | | (X-9)(x^2+5x+6)=0 | | 52/51/91:34 | | -16x+14x+13.5=5 | | 1000=16t^2+1900 | | X+50.3x-10= | | (6x+1)(2x+10)=180 | | 3(b-7)-2=3 | | (2x+10)+(6x+1)=180 | | 3f(-3)+h(5)= | | 9+-5x=4 | | -19+x=-19 | | -7(k-8)-(-8k+6)=-2 | | 20z-5-12x=10z+8 | | 1.5/6=3/x |

Equations solver categories